2020
DOI: 10.1111/pde.14472
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of recurrent Mycoplasma pneumoniae–induced rash and mucositis

Abstract: Mycoplasma pneumoniae (Mp) is a common cause of respiratory infections, which are accompanied by mucocutaneous manifestations in 20%-30% of cases. 1 These include Mycoplasma pneumoniae-induced rash and mucositis (MIRM), a condition distinct from the syndromes of erythema multiforme (EM) and Stevens-Johnson Syndrome (SJS) in terms of pathophysiology, presentation, treatment, and outcomes. 2 MIRM occurs secondary to an active Mp infection with prodromal symptoms of cough,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…A review of recurrent RIME cases showed that most cases started with an initial MP infection (Table 1 ). 6 , 8 , 9 , 11 , 12 Future studies could investigate whether persistently elevated antibodies from non‐MP pathogens could also increase risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of recurrent RIME cases showed that most cases started with an initial MP infection (Table 1 ). 6 , 8 , 9 , 11 , 12 Future studies could investigate whether persistently elevated antibodies from non‐MP pathogens could also increase risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent episodes are poorly understood. Reports have estimated a recurrence rate ranging from 9% to 38% 9 . In this report, we describe in detail two cases of recurrent RIME with initial episodes suspected to be triggered by MP.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nichtsdestotrotz führten diese teilweise auch zu Hospitalisierungen und verlängertem Krankheitsverlauf. Zwischen den Rezidiven lagen Zeitspannen von 2 Monaten bis zu 2 Jahren [ 28 ]. Ferner sind auch bei viral induzierten RIME Rezidive beschrieben, unter anderem 2 Fallberichte, in denen die initialen Episoden am ehesten durch Mycoplasma pneumoniae getriggert und die Rezidive teils durch Viren wie Influenza A und SARS-CoV‑2 ausgelöst wurden [ 50 ].…”
Section: „Reactive Infectious Mucocutaneous Eruptions“unclassified
“…MIRM gặp chủ yếu ở trẻ em, nam gặp nhiều hơn nữ (nam chiếm 2/3 tổng số trường hợp). 1,2,3 Cho đến nay, nguyên nhân gây ra MIRM chưa được biết đến chính xác. Một số giả thuyết cho rằng M. pneumoniae trực tiếp gây tổn thương các tế bào ở da và niêm mạc, một số giả thuyết khác lại cho rằng M. pneumoniae gián tiếp gây tổn thương thông qua cơ chế miễn dịch.…”
unclassified